歯学部学生における下顎骨エナメル上皮腫と角化嚢胞性歯原性腫瘍の鑑別診断に関する教育効果 - 木瀬, 祥貴; 内藤, 宗孝; 有地, 榮一郎; 森田, 光子; 勝又, 明敏; 有地, 淑子; 泉, 雅浩; 後藤, 真一 (Shika Hoshasen, 2010)
Objective: To clarify the educational effect of a lecture on differential imaging features comparing ameloblastomas and keratocystic odontogenic tumors of the mandibles presented to dental students.Methods: Panoramic and CT images of 10 ameloblastomas and 10 keratocystic odontogenic tumors were randomly presented 114 dental students. Test scores, correct answer ratios, identification index, and understanding of the imaging features contributing to a correct diagnosis were serially evaluated before and after the lecture on the differential imaging features comparing the two types of tumors.Results: The mean and standard deviation of the scoring ratios of dental students diagnosing these lesions on panoramic and CT images were 48.8 ± 10.8% and 52.5 ± 12.9%, respectively. After the lecture on the differential imaging features comparing the two tumors, the scoring ratios improved significantly. After the lecture, both the numbers of patients whose images were correctly diagnosed and the identification indices increased. The lecture also increased the number of imaging features recognized as contributing to the correct diagnosis.Conclusion: A lecture on the differential imaging features comparing ameloblastomas and keratocystic odontogenic tumors of the mandibles contributed to the improvement of imaging diagnosis skills among dental students.